Elderly patients admitted to secure forensic psychiatry services - Coid, J; Fazel, S; Kahtan, N (2002)
In a study of admissions to medium- and high-security from 7 of 14 health regions over a 7-year period, less than 2% were aged 60 years or over. These patients were atypical and highly selected, and half had committed homicide. Depressive illness, delusional disorder and dementia were the most prevalent diagnoses. The patients aged 60 and over had fewer previous convictions than younger patients, and were older when first admitted to psychiatric hospitals, usually in the context of their offending behaviour. The study suggests that some admissions to specialist services reflect an absence of more suitable provision for elderly patients at a lower level of security. Forensic psychiatry services were not involved with the growing number of elderly prisoners who are serving longer prison sentences and the needs of this group require further study.